Eight flute tunes from Butembo, east Belgian Congo: an analysis in two parts, musical and physical: Part 1 - Blacking, John (International Library of African Music, 1955)
The eight tunes were recorded by Mr. Hugh Tracey on July 24th, 1952, at Butembo, near Lake Edward, North-East Belgian Congo. The performer was Katsuba Mwongolo, a Nande herdsman who roams the highlands on the eastern border of the Congo where the hills run alongside the great western rift opposite the Ruwenzori Mountains. Mwongolo plays the flute all day to his goats and has developed, so they say, a distinct style of his own.
Keywords: Flute music; Music; Musical analysis; Ethnomusicology; Nande (Congolese (Democratic Republic) and Ugandan people); Flute; Musical instruments; History; Criticism; Belgian Congo; African Music; Flute (Instrument)